2022
DOI: 10.1007/s10803-021-05383-0
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Strategies and the Home Environment on Home Learning Experiences During the COVID-19 Pandemic in Children With and Without Developmental Disorders

Abstract: Using the Opportunity-Propensity Model (Byrnes in Dev Rev 56:100911, 2020 ; Byrnes & Miller in Contemp Educ Psychol 32(4);599–629, 2007 ), the current study investigated which factors helped predicting children’s home learning experiences during the COVID-19 pandemic, thereby examining differences between children with (DD; n = 779) and without (TD; n = 1443) developmental disorders. MANCOVA results indicated more negat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 143 publications
1
7
0
Order By: Relevance
“…Risk factors for increased psychiatric problems reported by Vasa et al included having an individual with COVID-19 diagnosed in the family, child understanding of COVID-19, and parent psychopathology. Children’s concern about COVID-19 was also reported by parents in the current study and by Baten et al ( 2021 ) as a factor impacting on their child’s mental health. However, Vasa et al did not measure other potential contributing factors such as changes to routines, support accessed, or changes to social and educational provisions.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Risk factors for increased psychiatric problems reported by Vasa et al included having an individual with COVID-19 diagnosed in the family, child understanding of COVID-19, and parent psychopathology. Children’s concern about COVID-19 was also reported by parents in the current study and by Baten et al ( 2021 ) as a factor impacting on their child’s mental health. However, Vasa et al did not measure other potential contributing factors such as changes to routines, support accessed, or changes to social and educational provisions.…”
Section: Discussionsupporting
confidence: 83%
“…Not only were they expected to learn whilst within an environment they typically associated with free time, but they were also required to attend to online instructional content, to apply a range of traditional and digital literacy skills, and to remain engaged while often having to inhibit any desires to use the same computer or tablet for their normal activities (e.g., playing games, watching videos; Stenhoff et al, 2020 ). Challenges due to teaching methods were also reported by Baten et al ( 2021 ) who identified that teaching strategies used in online were less effective for children on the autism spectrum. It is important that those teaching and supporting students on the autism spectrum recognise the potential negative impact on learning across this period and provide structured supports and opportunities to recover this time.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…One of the recommended directions which can support this effort is precisely -to strengthen national and subnational-level support to vulnerable groups‖ (OECD, 2021, p. 5). Among the key strategies recommended by the World Bank for the inclusive education sector planning, we can mention -the use of the twin-track approach‖ (Mcclain-Nhlapo, 2020, p.15), whose first step refers to -ensuring that mainstream education programmes are designed for all learners‖ (p.16) -a point of view relevant not only during and after the pandemic, but on a permanent basis;  Beyond age particularities, teenagers coming from economically disadvantaged groups present some needs and specific psycho-social characteristics, which manifest themselves more subtle and powerfully than in their peers and which have been intensified during the pandemic period, coming to the surface in the post- supporting students and parents in overcoming their prejudices about seeking and using counselling services; -forming/encouraging help-seeking behavior‖ (Brown et al, 2020, p. 23); guiding students towards acquiring/consolidating a so-called -sense of hope‖ (Brown et al, 2020) to give them energy and direction for their future actions; improving communication with and counselling of the students' families (Baten et al, 2022;Brown et al, 2020;Vockel & Ștefănescu, 2020); combining pre-pandemic approaches with newer, online approaches (lectures with parents, studies to analyze the needs of parents, online counsellors/meetings for parents and home visits); diversifying techniques by attracting -artistic media as an additional resource‖ (Loscalzo, 2022, 8) and making greater use of art therapies (drawing, sand therapy, theatre, music therapy -STAMP, 2018 -a very interesting and creative guide to achieving social inclusion for disadvantaged students using art techniques); combining face-to-face and digital techniques (Let & Brown, 2020): (individual counselling (online/face-to-face), form filling (online), interview (online, face-toface, phone), group counseling (online/face-to-face), peer counselling, vocational guidance, preventive counselling, and social assistance. Hence, the approaches will be ones which could lead in the medium and long term to the maintenance/recovery/initiation of well-being (Loscalzo, 2022;Bell et al, 2021) of the students from disadvantaged backgrounds.…”
Section: Introduction -Terminological and Paradigmatic Anchorsmentioning
confidence: 99%
“…For autistic young people in mainstream education, the forced removal from the sensory and social demands of the school environment might have facilitated learning in some cases (Heyworth et al, 2021; Simpson & Adams, 2022). Nonetheless, children with a range of neurodevelopmental differences experienced remote learning more negatively than neurotypical children in a parent-report survey study (Baten et al, 2022). The boundaries between home and school can be particularly important for autistic children, with home often experienced as a haven from societal demands.…”
mentioning
confidence: 99%